Hatchet II [videorecording (DVD)] - Green, Adam, 1975-; Harris, Danielle; Hodder, Kane Warren, 1955-; Shen, Parry, 1973-; Todd, Tony, 1952- (Dark Sky Films, 2011)
Marybeth, barely escapes the clutches of the mysterious, Crowley, who has already murdered her friends, and other vacationers in the New Orleans swamp country. She recruits a team of hired guns and returns to the bayou to exact revenge, but discovers that even with an army of hunters at her side, the murderous, Crowley cannot be contained. It will be up to her to defeat the seemingly indestructible, Crowley, but not before learning the truth about a twisted secret he shares with her own family!